Kinetics and mechanism of oxidative polymerization of 2-methylaniline - Ya. O. Mezhuev; Yu. V. Korshak; I. S. Strakhov; M. I. Shtilman; T. A. Vagramyan (Тонкие химические технологии, 2013)
The kinetics of oxidative polymerization of 2-methylaniline in hydrochloric acid aqueous solution in the presence of ammonium peroxydisulfate as the oxidant was studied. The presence of autocatalysis was demonstrated, and the reaction mechanism was suggested. On the basis of the mechanism a kinetic model of oxidative polymerization of 2-methylaniline was built. The model is in satisfactory agreement with the experimental results.